PEMANFAATAN LIMBAH RUMAH TANGGA MELALAUI USAHA SKALA MIKRO KECIL BAGI MASYARAKAT DI DAERAH ALIRAN SUNGAI (DAS) CITARUMDESA MULYASARI KECAMATAN CIAMPEL KABUPATEN KARAWANG - Ida Busnetty; Tulus T.H Tambunan; Sumiyarti Sumiyarti (Jurnal AKAL : Abdimas dan Kearifan Lokal, 2020)
Mulyasari Village, Ciampel District, Karawang Regency is one of the villages located in the Citarum watershed (DAS). Like other villages located in the watershed area, Mulyasari Village also faces a waste problem. One type is household waste. In most people in Mulyasari Village, all waste is deemed useless and must be disposed of. In fact, with proper management through micro and small scale businesses, waste can have economic value that can increase household income. In this regard, community service activities (PkM) regarding community economic empowerment through micro and small enterprises based on household waste are a response to efforts to provide solutions to the community regarding the problems faced by household waste. This PkM activity aims to introduce and disseminate the economic value of waste to the community, as the beginning of community empowerment activities more broadly. The form of activity is counseling and training and mentoring to achieve the objectives of the activity, the PkM implementation team uses communication and education methods using lecture and question and answer techniques and discussions. Activities have been running smoothly on September 19, 2019. The target partners of the activities are groups of the general public who are economically non-productive, with 46 participants. The participants responded positively to the PkM activity. The results of the evaluation of the activities recommended that this PkM program be continued with a follow-up PkM which was more directed at practical activities and mentoring